Faktor-Faktor Yang Mempengaruhi Terjadinya Obesitas Pada Residen Penyakit Dalam RSUD Dr. Zainoel Abidin - Tuti Sahara; Miniharianti; Dedy Fachrizal; Wardah (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Obesity is a condition that has an increased risk of morbidity and mortality from chronic diseases, cardiovascular disease, type II diabetes and colorectal disorders. Obesity is someone who has a body mass index > 25 kg/m. Purpose: This research is to determine the analysis of the factors that influence the occurrence of obesity. Research method: using explanatory research. Sampling using purposive sampling technique in order to obtain 63 respondents Resident of the Department of Internal Medicine. The tool used is a questionnaire containing questions: age, height (TB), weight (BB), examination of leptin levels. Data analysis used multiple linear regression test. The results of the bivariate analysis showed that there was a significant relationship between BMI and leptin, namely 0.05> 0.046, there was a significant relationship between obesity and gender, namely 0.05> 0.00, there was a significant relationship between obesity and leptin, namely 0.05 >0.00, and there was no significant relationship between obesity and fasting blood sugar, namely 0.05 <0.885. Conclusion: the factor associated with BMI is leptin levels. Researchers recommend using leptin results as an indicator of weight gain.